Producción agroecológica vs producción convencional : el problema de la creación de valor y el mercado. Discusión en perspectiva marxista (2018)
ABSTRACT: This article is intended to carry out a comparative exercise of the creation of values and production costs by taking as an object the crop of lettuce in a conventional peasant production and in an agro-ecological production. From there, a part of the theory of labor value, based on Marx’s ideas is put into discussion to try to show in which of the two types of crops, the work, measured in time, is greater. Based on this, an analysis of the real production costs is made and it is a matter of contributing to the discussion of the tendency of gentrification of the agro-ecological products. Two central categories are worked: food empires and agro-industrial system and, with the concept of imperialism being a part of both of them in order to understand the relation that agro-ecology has about the baseline laws of current social relations of production.